EFFECT OF NPK FERTILIZER DOSES ON ANTIOXIDANT AND ANTIMICROBIAL LEVELS OF SAMBUNG NYAWA (Gynura procumbens) - Mazid, Alwi; Umami, Wahyuni; AHS, Mirfat; Mohamed Nor, Moh Effendi; Raship, Izyani (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Gynura procumbens, commonly known as sambung nyawa, holds substantial medicinal value attributed to its diverse chemical compounds, including flavonoids, unsaturated sterols, triterpenoids, polyphenols, saponins, steroids, chlorogenic, caffeic, vanillic, para-coumaric acids, hydroxy benzoic acids, and essential oils. This study investigates the impact of NPK fertilizer dosages on sambung nyawa's antioxidant levels and antimicrobial activities. The research employed a Non-Factorial Randomized Complete Block Design (RCBD) with one treatment factor - NPK fertilizer dosage (N) at four levels. Results revealed significant effects of NPK fertilizer doses on leaf and total plant weights. Higher doses notably enhanced antimicrobial activity against various bacteria strains like E. coli, B. cereus, E. aerugenes, L. innocua, and S. aureus. Additionally, the plant exhibited strong antioxidant capabilities, demonstrating an IC50 DPPH scavenging activity of 2.112 mg/ml. This investigation provides crucial insights into optimizing NPK fertilizer dosages to boost sambung nyawa's antioxidant content and antimicrobial potency. The findings hold promise for agricultural practices and the potential utilization of this plant in health and medicinal realms.